(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
the works of the great poet and scientist Alisher Navoi are the object of research not only in literary studies and linguistics, but also in the fields of pedagogy. Because the main theme of Navoi’s literary heritage is personal perfection, and this issue is also the highest goal of pedagogy. Therefore, there is a lot of knowledge that pedagogues should learn from Navoi in the education of a perfect person. This article discusses the important role of wisdom from the works of Alisher Navoi in the education of the young generation. It is explained with examples that the topics of education and morals are reflected in wisdom on various topics.